The Pandemic Influenza Preparedness Framework: A viable procurement option for developing states?. (December 2017) - Eccleston-Turner, Mark
In this article, I argue that the Pandemic Influenza Preparedness (PIP) Framework is unlikely to have a significant impact on procurement of pandemic influenza vaccines by developing states during the next pandemic. I argue this on the basis that the vaccine stockpile that the Framework has created is not sufficiently large to meet the demand from developing states. I also argue that the fact that so few pandemic influenza vaccine manufacturers have committed to supply the PIP stockpile, and those that have, have given commitments lower than those initially proposed by the World Health Organization in the Framework, implies that the overall impact the PIP stockpile will have on procurement of pandemic influenza vaccines is even lower than initially anticipated within the literature.